PERLINDUNGAN HUKUM BAGI PENGGUNA JASA DRY CLEAN & LAUNDRY SERVICE TERHADAP HAK KONSUMEN (STUDI PUTUSAN NOMOR 85/PDT.G/2019/PN.JKT.PST) - Maya Adilla Humaira; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
Legal protection for consumers is very important because basically consumers have the same rights as business actors, both universal and specific rights. In Article 1 number 1 of Law Number 8 of 1999 concerning Consumer Protection, namely all efforts to ensure legal certainty to provide protection to consumers. Consumer protection is a legal instrument created to protect and fulfill consumer rights or efforts to ensure legal certainty to provide protection to consumers.